Causes and Consequences of Work Stress and Coping Behaviour of Employees : An Analysis - Arul Edison Anthony Raj, I.; Julius, Sheeba (Prabandhan: Indian Journal of Management, 2018)
Background : In the modern era, there is no job that is stress - free. Technological advancement and competitive market employees are forced to sustain their employment. It tends to increase their anxiety level as well as work tension. The banking industry is not an exceptional one. Objectives : The purpose of the study was to assess the causes and consequences of work stress and to investigate the individual and organizational coping strategies adopted for managing stress effectively. Materials and Methods : A sample of 186 participants (73.7% men and 26.3% women) from Dindigul Central Cooperative Bank (DCCB) participated in the study and the census method was adopted in the collection of data from individual respondents. Results: The results showed that the employees, to a greater extent, were satisfied with their family as well as work life. They had a very positive and good opinion regarding the fairness of the management systems and practices adopted by the bank. The employees attached top-priority to their work and ,therefore, they normally spent more time at work. The findings of the study suggested that to overcome the consequences of work-stress, the employees recommended measures that involved both individual and organizational level strategies. Conclusion: According to the respondents, the most appropriate solution to maintain work - life balance was capacity building and skill development on the part of the employees and involvement of employees in the organizational decision making.